PENGARUH PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK - Rinda Pratiwi (Jurnal Edukasi dan Penelitian Matematika, 2018)
Mathematical problem solving ability is the one of the ability that is expected can develop optimal in thestudents. However, based on result of observation and given test show that mathematical problem solving ability of students in the eighth grade MTsN Batusangkar has not developed optimally yet. One of the efforts is applying problem based learning (PBL). This research aims to reveal whether mathematical problem solving ability of the students applied the model of problem based learning is better than mathematical problem solving ability of the students who studied by using conventional learning.This instrument of research is final test. The analysis of final test indicated that mathematical problem solvingability of the students who were taught by using PBL model was better than mathematical problem solvingability of the students who studied by using conventional learning.Keywords–mathematical problem solving ability, problem based learning.